Educational D-N-A Game for the understanding of DNA and Biotechnology - Leong wan Vun; Chong Mun Ho; PeiklinTeoh; Amran Ahmed (Contemporary Research Center CRC Publications, 2013)
In order to promote understanding and sustain a keen interest in DNA and biotechnology among the younger generations in Malaysia, an educational and fun D-N-A card game was developed based on the principles of replication. This paper reports the preparation and also the setting up of the game